Numerical Analysis on Seismic Responses of a Large Metro Station in Sandy Area - Yu Liu; Xiao Liu (Advances in Civil Engineering)
A new assessment method is proposed considering shortcomings of the current investigations for the assessment of underground structures considering seismic load. First, the dynamic elastic modulus and damping ratio of sand are studied based on the dynamic characteristic experiment of the soil. Subsequently, a series of design acceleration time history curves are obtained using the proposed methods. Finally, the seismic response of underground structures is evaluated by a three-dimensional numerical simulation. The results indicate that the dynamic elastic modulus of sand decreases with the increase of dynamic elastic strain and increases with the increase of confining pressure. The influence of confining pressure on the damping ratio of sand is slight, but it can still be seen that the damping ratio decreases with the increase of confining pressure, especially when the dynamic elastic strain is relatively low. The interlayer displacement between the top and middle plate is 2.1 mm and the interlayer displacement angle is 1/2650. The interlayer displacement between the middle and bottom plate is 1.7 mm and the interlayer displacement angle is 1/4117. Under the action of fortification earthquake, the interlayer displacement angles of Taiyuan Street station are less than 1/550, indicating that the structure meets the seismic requirements.